Boron Foliar Application in Nutrition And Yield Of Beet And Tomato - Oliveira Gondim, Ancelio Ricardo de; Prado, Renato de Mello [UNESP]; Cecilio Filho, Arthur Bernardes [UNESP]; Alves, Adriana Ursulino; Ribeiro Correia, Marcus Andre (Taylor & Francis Inc, 2015)
The objective of this work was to evaluate the effect of the application of boron (B) by foliar spraying for the yield of beet (Beta vulgaris L.) and tomato (Solanum lycopersicum L.) crops. An experiment for each crop was done in a greenhouse at the Sao Paulo State University (UNESP), Jaboticabal campus, in Brazil. The experiments evaluated the B concentrations of 0, 0.085, 0.170, 0.255, and 0.340g L-1; applied in the 20, 35, and 50days after the transplant (DAT) of beet cv. 'Tall Top Early Wonder', and in the 20, 40, and 60 DAT for the tomato cv. 'Raisa N'. The plants were cultivated in pots with washed sand with 5dm(3) for the beet crop and 10dm(3) for the tomato crop. The beet and tomato crops were harvested 58 and 154 DAT, respectively. The leaves and fruits numbers; the foliar area; the dry matter of leaves, bark and roots; the fresh and dry matter of the fruits and the tuberous root; the dry matter of the total plant and the B foliar content were evaluated. The total dry matter of beet and tomato the plant were influenced by the concentration of the foliar B spray. The highest yield of the tuberous root and the total plant dry matter of beet occurred with B foliar concentration of 0.065g L-1 and it was associated with the B foliar content of 26mg kg(-1). The highest yield of fruit and total plant dry matter of tomato occurred with the B foliar spraying of 0.340g L-1 and it was associated with the B foliar content of 72mg kg(-1).
Keywords: trace element; foliar spraying; Solanum lycopersicum L.; Beta vulgaris L.; micronutrients; vegetables